The Respiratory Toxicities of Mustard Gas - Mostafa Ghanei; Ali Amini Harandi (Iranian Journal of Medical Sciences, 2010)
Sulfur mustard is one of the major potent chemical warfareagents. It was widely used against not only military personnelbut also civilian people of Iran during the last years (1984–1988) of the Iraq–Iran war. A number of studies were performedregarding the acute and long-term consequences ofsulfur mustard on respiratory system. Currently, many aspectsof leading respiratory disorder that was prescribed as “mustardlung” have been revealed. However, there is growing concernabout pathophysiological mechanisms behind the mustardlung. Herein available published materials about mustard lungare summarized, and it has been tried to highlight practicalpoints relevant to the diagnosis and treatment of the disease.Iran J Med Sci 2010; 35(4): 273-280.